Hydraulic and compressible flow turbomachines - Sayers, A. T. (London McGraw-Hill, 1990)
This book looks at turbomachines and how their performance is analysed and predicted. It is unique in its attempt to provide students with a comprehensive understanding of both hydraulic and compresible flow turbomachines, in contrast to competing texts that cover only compressible flow turbomachines. The text maintains a clear distinction between both types of machines throughout in both their design and operation.
Keywords: Turbomachines